Characterizing National Exposures to Infrastructure from Natural Disasters Data and Methods Documentation - Narayanan, Anu (RAND Corporation, 2016)
This report serves as the technical documentation and reference document for the data, methods, and analytic approach used in the analysis of national exposures to infrastructure from natural disasters. The analysis includes 11 natural hazards and five infrastructure sectors. Analytic findings about current and future exposures of infrastructure in the United States drawn from this data analysis are documented in a separate report.